RNA-binding is an ancient trait of the Annexin family - Patil, Sudarshan S.; Panchal, Vipul; Røstbø, Trude; Romanyuk, Sofya; Hollås, Hanne; Brenk, Ruth; Grindheim, Ann Kari; Vedeler, Anni (Frontiers in Cell and Developmental Biology, 2023)
Introduction: The regulation of intracellular functions in mammalian cells involves close coordination of cellular processes. During recent years it has become evident that the sorting, trafficking and distribution of transport vesicles and mRNA granules/complexes are closely coordinated to ensure effective simultaneous handling of all components required for a specific function, thereby minimizing the use of cellular energy. Identification of proteins acting at the crossroads of such coordinated transport events will ultimately provide mechanistic details of the processes. Annexins are multifunctional proteins involved in a variety of cellular processes associated with Ca2+-regulation and lipid binding, linked to the operation of both the endocytic and exocytic pathways. Furthermore, certain Annexins have been implicated in the regulation of mRNA transport and translation. Since Annexin A2 binds specific mRNAs via its core structure and is also present in mRNP complexes, we speculated whether direct association with RNA could be a common property of the mammalian Annexin family sharing a highly similar core structure. Methods and results: Therefore, we performed spot blot and UV-crosslinking experiments to assess the mRNA binding abilities of the different Annexins, using annexin A2 and c-myc 3′UTRs as well as c-myc 5′UTR as baits. We supplemented the data with immunoblot detection of selected Annexins in mRNP complexes derived from the neuroendocrine rat PC12 cells. Furthermore, biolayer interferometry was used to determine the KD of selected Annexin-RNA interactions, which indicated distinct affinities. Amongst these Annexins, Annexin A13 and the core structures of Annexin A7, Annexin A11 bind c-myc 3′UTR with KDs in the nanomolar range. Of the selected Annexins, only Annexin A2 binds the c-myc 5′UTR indicating some selectivity. Discussion: The oldest members of the mammalian Annexin family share the ability to associate with RNA, suggesting that RNA-binding is an ancient trait of this protein family. Thus, the combined RNA- and lipid-binding properties of the Annexins make them attractive candidates to participate in coordinated long-distance transport of membrane vesicles and mRNAs regulated by Ca2+. The present screening results can thus pave the way for studies of the multifunctional Annexins in a novel cellular context.